Optimizing combination dabrafenib and trametinib therapy in BRAF mutation‐positive advanced melanoma patients: Guidelines from Australian melanoma medical oncologists. (December 2016) - Atkinson, Victoria; Long, Georgina V.; Menzies, Alexander M.; McArthur, Grant; Carlino, Matteo S.; Millward, Michael; Roberts‐Thomson, Rachel; Brady, Benjamin; Kefford, Richard; Haydon, Andrew; Cebon, Jonathan
Abstract: BRAF mutations occur commonly in metastatic melanomas and inhibition of mutant BRAF and the downstream kinase MEK results in rapid tumor regression and prolonged survival in patients. Combined therapy with BRAF and MEK inhibition improves response rate, progression free survival and overall survival compared with single agent BRAF inhibition, and reduces the skin toxicity that is seen with BRAF inhibitor monotherapy. However, this combination is associated with an increase in other toxicities, particularly drug‐related pyrexia, which affects approximately 50% of patients treated with dabrafenib and trametinib (CombiDT). We provide guidance on managing adverse events likely to arise during treatment with combination BRAF and MEK inhibition with CombiDT: pyrexia, skin conditions, fatigue; and discuss management of CombiDT during surgery and radiotherapy. By improving tolerability and in particular preventing unnecessary treatment cessations or reduction in drug exposure, best outcomes can be achieved for patients undergoing CombiDT therapy.